A mechanistic view of human mitochondrial DNA polymerase γ: providing insight into drug toxicity and mitochondrial disease - Bailey, Christopher M. (2010)
Mitochondrial DNA polymerase gamma (Pol γ) is the sole polymerase responsible for replication of the mitochondrial genome. The study of human Pol γ is of key importance to clinically relevant issues such as nucleoside analog toxicity and mitochondrial disorders such as progressive external ophthalmoplegia. The development of a recombinant form of the human Pol γ holoenzyme provided an essential tool in understanding the mechanism of these clinically relevant phenomena using kinetic methodologies. This review will provide a brief history on the discovery and characterization of human mitochondrial DNA polymerase γ, focusing on kinetic analyses of the polymerase and mechanistic data illustrating structure-function relationships to explain drug toxicity and mitochondrial disease.